Frustrated Lewis Pairs Boosting Low-Temperature CO2 Methanation Performance over Ni/CeO2 Nanocatalysts - Xie, Yu; Chen, Jianjun; Wu, Xi; Wen, Junjie; Zhao, Ru; Li, Zonglin; Tian, Guocai; Zhang, Qiulin; Ning, Ping; Hao, Jiming (ACS catalysis, 2022)
Deciphering the relationship between the active-site structure and CO2 methanation mechanism over Ni-based catalysts faces great challenges. Herein, different distributions of frustrated Lewis pair (FLP) structures were precisely fabricated over Ni/CeO2-nanorods, Ni/CeO2-nanocubes, and Ni/CeO2-nanooctahedra to make progress in this issue. Ni/CeO2-nanorods presented the highest possibility for FLP construction among these catalysts due to their CeO2 (110) nature and the steric hindrance between the oxygen vacancy (OV) and hydroxyl species (OH). Compared to other samples with fewer FLPs, FLPs-enriched Ni/CeO2-nanorods showed a significantly higher CO2 conversion (84.2%) and a CH4 productivity of up to 147.1 mmol gcat –1 h–1 with a higher CH4 selectivity (97.8%) even at a temperature as low as 225 °C. As evidenced from systematical ex situ and in situ surface analysis results, this better low-temperature activity along with its acceptable stability was closely associated with the construction of catalytically active FLPs, which could effectively activate and convert CO2 via the cooperation of OV and OH. Also, the in situ (Raman and diffuse-reflectance infrared Fourier transform spectroscopy) analysis combined with density functional theory calculations further demonstrated that the copromotion of the emerged CO* route and formate pathway was responsible for the promising low-temperature (≤225 °C) methanation performance over the FLP-enriched Ni/CeO2-nanorods. Such CO2 activation by FLPs will potentially guide the design of CO2 hydrogenation catalysts.